When Time on Task Is Seen as a Reward: Autonomous Motivation Increases Preference for Pursuing Goals More Often for Less Time - Johanna Peetz; Marina Milyavskaya; Mariya Davydenko (Collabra: Psychology, 2020)
When working towards goals, the length and frequency of goal pursuit sessions might play a role in individuals’ goal pursuit motivation. We examined whether a more divided (frequent, shorter sessions) or a cumulated (less frequent, longer sessions) goal pursuit schedule increases people’s motivation to work towards personal goals. Across two studies (N = 448), the underlying reasons for pursuing the goal mattered. A divided schedule was more motivating than a cumulated schedule if participants reported highly autonomous reasons (pursuing a goal due to personal interest or values), but the difference was eliminated for those reporting low autonomous reasons. We discuss how perceiving time spent on goal activities as loss, reward, or investment may explain scheduling preferences and how these may map on to preferences for scheduling financial losses and rewards outlined by prospect theory.